Key Green Chemistry research areas from a pharmaceutical manufacturers' perspective revisited. Issue 22 (2nd November 2018) - Bryan, Marian C.; Dunn, Peter J.; Entwistle, David; Gallou, Fabrice; Koenig, Stefan G.; Hayler, John D.; Hickey, Matthew R.; Hughes, Shaun; Kopach, Michael E.; Moine, Gerard; Richardson, Paul; Roschangar, Frank; et al.
Abstract : The ACS Green Chemistry Institute® Pharmaceutical Roundtable has assembled an updated list of key research areas to highlight transformations and reaction media where more sustainable technologies would be most impactful. Abstract : In 2007 the members of the ACS Green Chemistry Institute® Pharmaceutical Roundtable assembled a list of key green chemistry research areas to both identify transformations that would benefit from improvements in process greenness and to encourage academic research to this end. The list provided the topics for a review of the literature, published in 2007 in the journal Green Chemistry. As part of the 10th anniversary of the founding of the Roundtable in 2015, the membership revisited the list. This article discusses the selection of the revised list, the updated 10 key green chemistry research areas, 2 solvent themes and the emerging area of medium molecules that resulted from the exercise.